Tropical seasonal changes impact on hematological parameters of goats - Dhuha, J. M.; Muayad, M. T. A.; Saeed, O. A.; Al-Bayar, M. A.; Saeid, Z. J. M.; Al-Bakri, S. A.; Che Musa, H.; Safaa, A.; Abed, Q. N.; Kaabi, S. A. G.; Haniza, H. M. Z.; Shaari, A. (Diponegoro University, 2021)
The study was carried out to evaluate the impact of seasonal variations on the hematological responses of goats in Malaysia. Fifty-two goats (24 bucks and 28 does), aged between 1 to 2 years old were used in the study. The goats were fed on commercial concentrate and forage, access to mineral salt and water was ad libitum. Blood samples were obtained from each goat in January, May and September to analyze hematology blood constitute during the study. The results showed that red blood cell (RBC) levels in Anglo-Nubian females rose dramatically in January and May while the Saanen breed remains without diversity. In all seasons, high hemoglobin (Hb) concentration of Anglo-Nubian males was unlike Saanen breed. For Saanen females, mean corpuscular volume (MCV) increased significant-ly, whereas in Saanen males, mean corpuscular hemoglobin (MCH) and MCH concentration (MCHC) were increased. High packed cell volume (PCV) concentration of Anglo females compared to others during September. In conclusion, variations in breed and sex of goats reflect the distinct ability of trop-ical changes that have been formed during seasonal effects on hematological responses between the two breeds of goats.